Computational Models in Engineering - Volkov, Konstantin (IntechOpen, 2020)
The accurate prediction of multi-physical and multi-scale physical/chemical/mechanical processes in engineering remains a challenging problem despite considerable work in this area and the acceptance of finite element analysis and computational fluid dynamics as design tools. This book intends to provide the reader with an overview of the latest developments in computational techniques used in various engineering disciplines. The book includes leading-edge scientific contributions of computational and applied mathematics, computer science and engineering focusing on the modelling and simulation of complex engineering systems and multi-physical/multi-scale engineering problems. The following topics are covered: numerical analysis and algorithms, software development, coupled analysis, multi-criteria optimization as they applied to all kinds of applied and emerging problems in energy systems, additive manufacturing, propulsion systems, and thermal engineering.